Spatial Heterogeneity of Food Security in Indonesia: Unpacking the Roles of Technology and Democracy Index - Wicaksono, Ditto Satrio; Pusponegoro, Novi Hidayat; Setiyawan, Arbi (Politeknik Statistika STIS, 2025)
Introduction/Main Objectives: Food security is a key concern for all countries, especially Indonesia. Technological development and democratic quality are vital for sustainable food security. This study aims to determine the impact of technology and democracy on food security. Background Problems: The relationship between food security and these two factors remains uncertain. Moreover, the extant literature on the spatial impacts on food security yields results that are inconclusive. Novelty: This study offers a comprehensive depiction of the impact of spatial relationships between variables, with a particular focus on the quality of democracy and technology, on the multidimensionality of food security. Research Methods: A spatial lag model is applied to ascertain the impact of technological and democratic on multidimensional food security using data from 34 provinces in 2022. Finding/Results: The results reveal significant spatial dependence in Indonesia’s food security. Technological development and democratic quality positively and significantly affect food security, while urbanization and food crop land expansion show negative and positive effects, respectively. Spatial spillover accounts for approximately 37%–38% of the total impact of each explanatory variable. These findings suggest that technology adoption, democratic strengthening, and interprovincial collaboration are crucial for improving food security.